2006
DOI: 10.1111/j.1651-2227.2006.tb02292.x
|View full text |Cite
|
Sign up to set email alerts
|

A boy with coeliac disease and obesity

Abstract: Aim: To report the case of a 14‐y‐old boy with coeliac disease and obesity. Methods and results: A 14‐y‐old boy presented with episodic diarrhoea associated with eating spaghetti. His body mass index (BMI) at presentation was 37.2 kg/m2 (>99.9th centile). Both antigliadin and anti‐endomysial antibodies were positive, and coeliac disease was diagnosed by jejunal biopsy. His diarrhoea ceased and the gliadin and endomysial antibodies disappeared after starting gluten‐free diet. At 17 y, his BMI increased to 42.7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 8 publications
0
7
0
1
Order By: Relevance
“…Semeraro et al (14) described a 14‐year‐old girl with CD who gained excessive weight after starting on a GFD, and speculated that the parental urge to improve her previous undernourishment led to increased caloric consumption and obesity (14). Oso et al (15) reported on a 14‐year‐old boy with diarrhea and obesity. On a GFD his BMI increased from 37 to 42.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Semeraro et al (14) described a 14‐year‐old girl with CD who gained excessive weight after starting on a GFD, and speculated that the parental urge to improve her previous undernourishment led to increased caloric consumption and obesity (14). Oso et al (15) reported on a 14‐year‐old boy with diarrhea and obesity. On a GFD his BMI increased from 37 to 42.…”
Section: Discussionmentioning
confidence: 99%
“…On a GFD his BMI increased from 37 to 42. The authors noted that patients on GFD take excessive energy in the form of fats and high‐energy drinks because of the expense and unpalatability of GFD (15). Czaja‐Bulsa et al (16) described an 18‐year‐old obese boy with increased obesity after GFD for 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…New extraintestinal symptoms have gained importance and casefinding strategy in high-risk groups (subjects with refractory iron-deficiency anemia, osteoporosis, increased transaminase levels, autoimmune disease, family history and other associated conditions) often leads to diagnosis before overt malnutrition can take place. Some reports in the literature also suggest that CD and obesity can coexist in both childhood and adolescence (Conti-Nibali et al, 1987;Franzese et al, 2001;Oso and Fraser, 2006;Arslan et al, 2009). Furthermore, patients with CD who have normal nutritional status, or are overweight at presentation, would be at further risk of obesity after gluten-free diet (GFD) because of improved intestinal absorption and unbalanced diet rich in lipids and proteins (Mariani et al, 1998;Dickey and Kearney, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Özellikle son iki dekatta yapılan ulusal ve uluslar arası çalışmalarda da çölyak hastalarının yaş ortalamasının arttığı ve Bu çalışmada, çölyak hastalığına eşlik ettiği bilinen klasik hastalıklara ek olarak 3 hastada obesite saptandı. Özellikle son yıllarda literatürde, obes çocuklarda tedaviye dirençli demir eksikliği anemisi, tekrarlayan karın ağrısı, transaminaz yüksekliği ve makarna yedikten sonra ishal görülmesi gibi nedenlerle çölyak serolojisi veya endoskopi yapılarak çölyak hastalığı tanısı konulan olguların sunumları bulunmaktadır (19)(20)(21)(22)(23). Ayrıca, yapılan az sayıda çalışmada da çocuklarda çölyak hastalığı tanısı konduğunda obesite sıklığının %0-6 arasında; kilo fazlalığının ise %8-20 arasında değiştiği saptanmıştır (9,(24)(25)(26)(27)(28)(29).…”
Section: Discussionunclassified